Baddeleyite microstructural response to shock metamorphism in three enriched shergottites and implications for U-Pb geochronology - Sheen, Alex I.; Herd, C. D. K.; Staddon, L. G.; Darling, J. R.; Schwarz, Winfried H.; Tait, K. T. (Geochimica et cosmochimica acta, 2024)
Baddeleyite (monoclinic zirconia; m-ZrO2) occurs as a late-stage accessory mineral in shergottites and has been used to determine U-Pb igneous crystallization ages via in-situ secondary ion mass spectrometry (SIMS). During shergottite ejection from the surface of Mars, baddeleyite develops a range of microstructures primarily due to a series of shock-induced transformations to high pressure and temperature polymorphs. It remains poorly constrained to what extent U-Pb systematics in baddeleyite are sensitive to shock conditions experienced by shergottites. To investigate this, we examined baddeleyite in the enriched shergottites Jiddat al Harasis (JaH) 479, Northwest Africa (NWA) 10299, and NWA 12919, which bridge the gap in shock conditions represented in previous microstructural studies. Electron backscatter diffraction (EBSD) analysis reveals that although some baddeleyite grains retain magmatic microstructures (i.e. homogenous crystallographic orientations and twinning of igneous origin), there is widespread phase transformation to high-pressure orthogonal polymorphs (o-ZrO2) followed by reversion. JaH 479 contains more grains with preserved magmatic microstructures than the other two shergottites, suggesting that it experienced lower bulk shock pressures. Nanometer-scale reverted m-ZrO2 in NWA 10299 and NWA 12919 further points to insufficient post-shock temperatures; this contrasts with JaH 479 where greater variation in local temperature conditions enabled the development of µm-scale domains of reverted m-ZrO2. Individual grains that are separated into two distinct microstructural domains may reflect controls on shock propagation due to relative density contrast among the surrounding phases. SIMS U-Pb baddeleyite analysis yields igneous crystallization ages of 210 ± 9 Ma (JaH 479), 196 ± 11 Ma (NWA 10299), and 188 ± 11 Ma (NWA 12919). At the SIMS resolution, we find no clear evidence for significant Pb loss in the surveyed baddeleyite grains, suggesting that temperatures during the formation of both nm-scale and µm-scale reverted m-ZrO2 in the three shergottites were insufficient to cause significant Pb diffusion. Given the robust baddeleyite U-Pb isotope systematics in the majority of shergottites dated by SIMS methods thus far, we argue that shock conditions experienced by the bulk of shergottites were insufficient to introduce significant U-Pb isotopic mobility, which is limited to grains showing microstructural evidence for extensive post-shock heating and recrystallization. Our findings place new constraints on baddeleyite microstructural response to shock conditions of shergottite ejection and demonstrate that microstructural observations are critical when using baddeleyite as a chronometer in shocked planetary materials.
Gesehen am 05.08.2024